Analysis of Teacher Problems in Implementing The Kurikulum Merdeka in The Learning Process - Purbadianti, Novela Hayunda; Ahdhianto, Erif; Barus, Yohannes Kurniawan (Universitas Negeri Malang, 2024)
Curriculum changes often give rise to new challenges. Therefore, in changing this curriculum, schools as implementers of the educational process are required to have a deeper understanding of the content and objectives of the new curriculum. The aim of this research is to determine: (1) the implementation of the Kurikulum Merdeka; (2) obstacles faced by teachers in implementing the Kurikulum Merdeka; (3) teacher efforts to overcome problems related to the implementation of the Kurikulum Merdeka. Researchers used a qualitative descriptive methodology. The data collection process uses techniques such as observation, interviews and documentation. The results of this research are: (1) The Merdeka Curriculum has been implemented at SDN 1 Gador for approximately two years in stages; (2) Teachers experience difficulties in making learning plans, choosing teaching methods and strategies that are appropriate for students, and designing assessment and evaluation instruments when implementing the Kurikulum Merdeka; (3) To overcome these problems, teachers use strategies such as discussing difficulties in KKG forums, making reflection journals, and making class agreements. Keywords: teacher; problems ; curriculum